THE INFLUENCE OF MARKET SEGMENTATION ON CUSTOMER DECISIONS IN CHOOSING BANK SYARIAH INDONESIA IN NORTH LUWU REGENCY - Sahrir, Sukmawati Sultan (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2024)
AbstractThe Influence of Market Segmentation Based on Geography, Demographics, Psychographics, and Behavior on Customer Decision in Choosing Islamic Banks in North Luwu Regency